2021
DOI: 10.1177/03000605211004759
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for 28-day mortality in patients with sepsis-related myocardial injury in intensive care units

Abstract: Objective This study aimed to identify the risk factors for death in patients with sepsis-related myocardial injury. Methods A retrospective study was conducted in 158 patients with sepsis-related myocardial injury in a mixed medical intensive care unit from January 2009 to March 2020. The patients were divided into those who survived and those who died on the basis of whether they survived after 28 days. Demographic and clinical parameters were collected. Multivariate logistic regression was performed. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…As mentioned before, PaO 2 /FiO 2 as one of items in SOFA score could reflect the severity of illness. Some studies have shown that PaO 2 /FiO 2 was an independent risk factor for 28-day death in patients with sepsis [ 9 , 10 , 20 ], which was also confirmed our study. However, there was a U-shape relationship between PaO 2 /FiO 2 and 28-day mortality in patients with sepsis through analysis using generalized additive model and smoothed curve fitting.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As mentioned before, PaO 2 /FiO 2 as one of items in SOFA score could reflect the severity of illness. Some studies have shown that PaO 2 /FiO 2 was an independent risk factor for 28-day death in patients with sepsis [ 9 , 10 , 20 ], which was also confirmed our study. However, there was a U-shape relationship between PaO 2 /FiO 2 and 28-day mortality in patients with sepsis through analysis using generalized additive model and smoothed curve fitting.…”
Section: Discussionsupporting
confidence: 92%
“…A retrospective study of 135 elderly patients with sepsis showed that PaO 2 /FiO 2 was a promising tool and biomarker for predicting 28-day mortality [ 9 ]. High PaO 2 /FiO 2 was an independent risk factor for 28-day mortality in patients with sepsis-related myocardial injury [ 10 ]. In addition, a novel blended machine learning (ML) model for hospital mortality prediction in ICU patients with sepsis identified the minimum PaO 2 /FiO 2 as one of the top important predictors [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…SpO 2 and PaO 2 were also independent predictors for predicting the mortality of septic patients with AF. Previous studies have shown that SpO 2 and PaO 2 were associated with mortality of many diseases including aortic dissection, acute respiratory distress syndrome, and sepsis-induced myocardial injury (35)(36)(37). In addition, first 24-h urine output was also a risk factor associated with the prognosis of septic patients with AF.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria were as follows. I diagnosis of septic shock according to the sepsis-3 definition [ 7 ] on admission to the ICU; II cardiac troponin I (cTnI) levels >0.04 ng/mL (detected by the PATHFAST chemiluminescence immunoassay; Hangzhou Red Cross Hospital, Zhejiang, China) on admission to the ICU [ 8 ]; III age ≥18 years. …”
Section: Methodsmentioning
confidence: 99%
“…II cardiac troponin I (cTnI) levels >0.04 ng/mL (detected by the PATHFAST chemiluminescence immunoassay; Hangzhou Red Cross Hospital, Zhejiang, China) on admission to the ICU [ 8 ];…”
Section: Methodsmentioning
confidence: 99%